2022
DOI: 10.1002/pul2.12163
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced pulmonary hypertension upregulates eNOS and TGF‐β contributing to sex‐linked differences in BMPR2+/R899X mutant mice

Abstract: Dysfunctional bone morphogenetic protein receptor 2 (BMPR2) and endothelial nitric oxide synthase (eNOS) have been largely implicated in the pathogenesis of pulmonary arterial hypertension (PAH); a life‐threatening cardiopulmonary disease. Although the incident of PAH is about three times higher in females, males with PAH usually have a worse prognosis, which seems to be dependent on estrogen‐associated cardiac and vascular protection. Here, we evaluated whether hypoxia‐induced pulmonary hypertension (PH) in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…EC injury in IPAH and animal models of hypoxia-induced PH is associated with Cav-1 phosphorylation and depletion via shedding of extracellular vesicles into the circulation (13). Despite previous studies' findings on EC-Cav-1/ BMPR2 depletion as an important switch towards endothelial dysfunction (21,31,35), more specific information about what triggers the process remains unclear. Here, we observed that pathogens can contribute to EC-Cav-1/BMPR2 depletion and initiate Sch-PAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EC injury in IPAH and animal models of hypoxia-induced PH is associated with Cav-1 phosphorylation and depletion via shedding of extracellular vesicles into the circulation (13). Despite previous studies' findings on EC-Cav-1/ BMPR2 depletion as an important switch towards endothelial dysfunction (21,31,35), more specific information about what triggers the process remains unclear. Here, we observed that pathogens can contribute to EC-Cav-1/BMPR2 depletion and initiate Sch-PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BMPR2 deficiency is known to promote cell death, endothelial-to-mesenchymal transition (endoMT), and abnormal proliferation of pulmonary vascular cells, including ECs, which contribute to the severe pulmonary vascular remodeling observed in several subgroups of PAH ( 29 33 ). Moreover, it has been shown that heterozygous Bmpr2 +/− mice have increased S. mansoni egg translocation in the lungs via enlarged hepatic sinusoids ( 34 ), and Bmpr2 +R899X loss-of-function mutant mice develop “spontaneous” PH, reinforcing the crucial role of this signaling pathway in the development of PAH, including the infectious disease ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…PAH patients are found to be associated mostly with altered bone morphogenetic protein receptor type 2 (BMPR2) (a transmembrane serine/threonine kinase family gene), 58,59 G protein coupled receptor (GPCR) related genes (a large family encoding surface receptors), 60 pyruvate dehydrogenase kinase 4 (PDK4) (protein kinase family) 61 and transforming growth factor beta (TGF-b) signaling pathways. 62 Several studies have indicated an association between these genes and hypoxic pathways, [63][64][65] which is one of the hallmarks of PH. The primary transcriptional response to hypoxic stress is mediated by the hypoxia-inducible factors (HIFs).…”
Section: Transcriptomics In Phmentioning
confidence: 99%
“…TGF-b is found to be highly upregulated in both medial and intimal layers of remodelled pulmonary vessels. 63,69 The importance of both BMPR2 and TGF-b has been implicated in PH pathophysiology.…”
Section: Transcriptomics In Phmentioning
confidence: 99%